Determination of remaining strength of corroded pipeline using closed – form solution - Nur Fariza, Talib (2013)
Corrosion has become a main issue for all engineering sector in these decades. Failure due to corrosion has been one of the greatest concerns in maintaining the pipelines integrity. Therefore, corrosion defects must be accurately evaluated in order to avoid economic loss and environmental damages. It is very important to know the value of the maximum pressure which is critical application to considering in its design for safety and reability. The main purpose of this project is determine remaining strength of corroded pipeline using closed- form solution. New methods which is NEW UMP have been predict and applied compared with other method on difference literature that contain with difference material, gouge length, depth, outer diameter. The results obtained show that the NEW UMP has given the positive result for every criterion that has been test. NEW UMP also predict almost similar and closed with burst pressure value.